APPLICATION OF WEB BASED VE.RUBRIC TO THE PERFORMANCE ASSESSMENT MAKING BED IN SMK HOTEL ACCOMODATION - Rohaeni, Neni; Jubaedah, Yoyoh; Rinekasari, Nenden Rani; Fahliani, Ihfa Siti (Universitas Pendidikan Indonesia, 2021)
This background of this research is motivated by the fast moving technology development of the education world which implicates the development standard development of performance assessment in assessing student's competence in SMK Hotel Accommodation, so the result of performance assessment could be well documented for a long time. The purpose of this research is to develop a Web-Based VE.Rubric to the Making Bed Performance Assessment Application in SMK Hotel Accommodation. This research is using descriptive method with the planning, production, and evaluation phase. Data collecting technique was used by utilizing interview and validation test through Expert Judgement to IT Expert, Assessor, Teacher, and Hotel Practitioner as Housekeeping's Expert. The result of the shows that VE.Rubric to the Making Bed Performance Assessment is considered worthy to be implemented to the performance test in SMK Hotel Accommodation and the in the Hotel Industry to the Job Performance Housekeeping Department.Keywords: VE.Rubric, Web based application, Performance assessment, Making bed, SMK Hotel AccommodationÂ